Creating a national space: about the first initiatives of building of the Saint Sava temple in Belgrade. A comparative approach - Feder, Aleksandra (Balcanica Posnaniensia. Acta et studia, 2020)
In the article are considered ideological and identity aspects of the emergence of the initiatives to build an Orthodox temple dedicated to Saint Sava in Belgrade. The object was thought to become an emblem of the reconstructed Serbian identity, created on the basis of national and religious narratives from the 19th and 20th century. The issue is showed comparatively with the Ivan Meštrović artistic project entitled Vidovdanski Hram, dedicated to the idea of Yugoslav unity.